Catalytic pyrolysis of the Eupatorium adenophorum to prepare photocatalyst-adsorbent composite for dye removal. (10th June 2019) - Cheng, Song; Hu, Wenhai; Srinivasakannan, C.; Xia, Hongying; Zhang, Libo; Peng, Jinhui; Zhou, Junwen; Lin, Guo; Zhang, Qi
Abstract: Eupatorium adenophorum, a kind of pernicious weed, is used to produce a photocatalyst-adsorbent composite, consisting of ZnOFe3 O4 particles on the surface of activated carbon, and bio-gas via catalytic pyrolysis. The photocatalyst-adsorbent composite was characterized by several characterization methods. The results show that the photocatalyst-adsorbent composite possesses adsorptive, photocatalytic degradative and magnetic properties. Methylene blue, a kind of dye, is used to evaluate the adsorption and photocatalytic degradation performance of photocatalyst-adsorbent composite. The maximum amount of methylene blue adsorption in photocatalyst-adsorbent composite was as high as 330.03 mg/g based on the adsorption experiment in dark conditions. The photocatalyst-adsorbent composite had good degradation performance with methylene blue, which was found to be 20.78% more efficient than the ZnO catalyst and 205% more efficient than the adsorption under ultra violet light irradiation. Photocatalyst-adsorbent composite could be conveniently separated from the aqueous solution by using an external magnetic field. The bio-gas was collected from the pyrolysis process, which mainly consisted of H2 and CO. The production cost of the photocatalyst-adsorbent composite is US$ 1, 361/t based on the preliminary economic analysis. Graphical abstract: Figure shows the mechanism of the methylene blue photodegradation using photocatalyst-adsorbent composite.Image 1 Highlights: Novel photocatalyst-adsorbent composite is reported for methylene blue treatment. The photocatalyst-adsorbent composite exhibits 20.78% more efficient than ZnO in methylene blue removal. Mechanism of the methylene blue photocatalytic degradation process is shown.